Evaluation of poisoning cases admitted to pediatric emergency department - Bork, Turgay; Kara, Aslıhan (My University, 2021)
In our study, it was aimed to compare the demographic and clinical characteristics of pediatric poisoning cases admitted to a university hospital with the literature and to discuss the problems encountered in forensic reports issued for such cases. Our study is a retrospective descriptive study. It consists of 715 children who were admitted to our university hospital between 2012 and 2018 due to poisoning. Poisoning is responsible for 36.0% of all pediatric forensic cases. 57.8% (n = 413) of 715 cases were male. The mean age was 7.38 ± 2.45 years. The most common causes of poisoning were drug intake with 55.5% (n = 397) and corrosive substance intake with 41.0% (n = 293), respectively. 3.2% (n = 23) of the cases had ingested drugs for suicidal purposes. Most frequent admissions to the hospital occurred during July and August. 26.2% (n = 187) of the cases were followed up in the intensive care unit. Most poisoning cases (41.4%, n = 296) occurred between 12:00 and 18:00. Comparison of the differences between the temporary and final forensic reports of our cases showed that there was a difference of 2.1% for life-threatening cases and 6.0% for cases that can be resolved with simple medical intervention. Poisoning constitutes a significant proportion of pediatric forensic cases. The majority of cases were poisoned accidentally. The ingestion of medicinal drugs and household cleaning products seems to be the most common cause of poisoning. Such medicines and cleaning products should be kept closed and out of the reach of children. The completion of the clinical and laboratory findings of the case should be awaited before reports of pediatric forensic cases are issued. This prevents the emergence of contradictory reports.
Keywords: Adli Tıp; Pediatri